Isaac's storm : a man, a time, and the deadliest hurricane in history - Larson, Erik.; Cline, Isaac Monroe (New York : Vintage Books, 2000)
Tells the story of Isaac Cline, a weather scientist in Galveston, Texas in 1900, discussing his belief and assertion that nothing in the way of weather could destroy the coastal city; and looks at how Cline dealt with the aftermath of the hurricane that hit Galveston on September 8, claiming the lives of thousands of people.
Based on the diaries of Isaac Monroe Cline and on contemporary accounts.
Includes bibliographical references (p. 307-313) and index.
Booklist
Library Journal Starred
School Library Journal
Young Adult
Keywords: Cline, Isaac Monroe; Cline, Isaac Monroe; Floods -- Texas -- Galveston -- History -- 20th century; Hurricanes -- Texas -- Galveston -- History -- 20th century; Floods -- Galveston (Tex.) -- History; Hurricanes -- Galveston (Tex.) -- History; Galveston (Tex.) -- Biography; Galveston (Tex.) -- History -- 20th century; Galveston (Tex.) -- Biography; Galveston (Tex.) -- History